The multigenerational workplace communicate, collaborate, and create community - Abrams, Jennifer; Von Frank, Valerie (Thousand Oaks, California Corwin, 2014)
Collaboration between professionals of all generations is an essential factor in school success. What do Boomers need from younger generations? What do GenXers and Millennials have to offer Boomers? Each generation wants to contribute and to feel empowered. The youngest generation wants an equal voice; Boomers want to leave a legacy; GenXers want to make a difference.This book, based on a very popular workshop that Abrams has presented across the U.S. and Canada, will address how all educators can look through a generational filter to be more effective communicators, teachers and administrators; to help retain those who may be more easily frustrated at their lack of immediate success; and to plan for succession by future generations of leaders.Concrete tools are key elements of the book, helping readers to define the generations and their needs, to identify themselves on the continuum, and to plan ways to bridge generational differences.
Introduction: Lost in translation -- Defining the generations -- Working with multiple generations -- School savvy etiquette -- Communicate to collaborate -- Recruiting and retaining the generations -- Differntiating professional learning for the generations -- Succession planning.
Includes bibliographical references (pages 131-140) and index.
Keywords: Communication in education; Intergenerational communication; Teachers -- Professional relationships; Educational leadership; Communication in management; Intergenerational relations; Employees -- Training of; Diversity in the workplace; Supervision of employees